Respuesta :
the formula is (x-h)^2+(y-k)^2=r^2
so, using this, and knowing that h is -3 and k is -5 and r is 4, we get
(x--3)^2+(y--5)^2=(4)^2, which equals
(X+3)^2+(y+5)^2=16
:)
so, using this, and knowing that h is -3 and k is -5 and r is 4, we get
(x--3)^2+(y--5)^2=(4)^2, which equals
(X+3)^2+(y+5)^2=16
:)
Answer:
[tex](x+3)^2+(y+5)^2= 16[/tex]
Step-by-step explanation:
the equation of a circle with Center -3, -5 and radius 4
center is (-3, -5) and radius = 4
Equation of a circle is
[tex](x-h)^2+(y-k)^2= r^2[/tex]
Where (h,k) is the center and r is the radius of the circle
Given center is (-3, -5) . h= -3 and k= -5
WE plug in the value of h , k and r
[tex](x-h)^2+(y-k)^2= r^2[/tex]
[tex](x-(-3))^2+(y-(-5))^2= 4^2[/tex]
[tex](x+3)^2+(y+5)^2= 16[/tex]